Evaluation of interfacial sulfate complexation by a bis-thiourea ionophore at water-organic interfaces using microelectrochemistry and high resolution mass spectrometry - Alvarez de Eulate; Busetti, F.; Arrigan, Damien (Elsevier, 2017)
Simple, fast and low cost methods for the detection of sulfate are required for different applications. Electrochemistry at water/o-nitrophenyloctylether (W/NPOE) interfaces was employed to evaluate sulfate detection by ionophore-facilitated ion-transfer at an array of micro-interfaces. With ionophore 1,3-[Bis(3-phenylthioureidomethyl)]benzene present in the NPOE phase, the transfer of sulfate across the interface was determined by voltammetry at ca. - 0.35 V for 0.01 M Na2SO4 on the Galvani potential scale. The potentiometric detection limit for sulfate was 0.6 × 10- 6 M, based on the shift in the half-wave transfer potential with concentration. Amperometric detection limits for forward and reverse ion transfer currents were determined to be 14 × 10- 6 M and 0.8 × 10- 6 M, respectively. Electrochemical analysis of the half-wave potential versus logCSO42 -w and the corresponding electrospray ionisation – high resolution mass spectrometry (ESI-HRMS) analysis of W/NPOE emulsions indicated interfacial complexation via the formation of 1:1 sulfate:ionophore complexes. ESI-HRMS analysis of W/NPOE emulsions formed with water samples from an advanced water treatment plant revealed the binding of the ionophore to potential interferences from this environment, thus providing a guide to sensor development.